Nursing of a patient with COPD complicated with type II respiratory failure treated by sequential non-invasive positive pressure ventilation via nasal high-flow oxygen therapy (经鼻高流量氧疗序贯无创正压通气治疗1例COPD合并Ⅱ型呼吸衰竭患者的护理) - QIAO Xinli (乔新立); MA Hailian (马海莲); LI Na (李娜); CHEN Hong (陈宏); TANG Ling (唐玲); ZHANG Ning (张宁); WANG Jingjing (王晶晶); ZHANG Tingting (张婷婷); ZHOU Jie (周洁) (中西医结合护理)
This paper summarized the nursing measures for a patient with chronic obstructive pulmonary disease complicated with type II respiratory failure treated by sequential non-invasive positive pressure ventilation via nasal high-flow oxygen therapy. Nursing interventions were carried out in the following ways: non-invasive positive pressure ventilation, medication nursing, enteral nutrition support, pipeline maintenance, skin care and psychological nursing and other issues. Efforts were made to improve the respiratory failure status and various vital signs, control of carbon dioxide retention and reduce the occurrence of complications. By providing patients with a constant, adjustable, high-speed breathing gas mixture formed from air and oxygen, it was aimed to crush the gas left in the nasal cavity, oral cavity and pharynx, and significantly reduce the amount of carbon dioxide inhaled during the next inhalation. The application of sequential treatment with transnasal high-flow oxygen therapy has achieved positive therapeutic results in patients with hypoxic respiratory failure. (本文总结经鼻高流量氧疗序贯无创正压通气治疗1例慢性阻塞性肺疾病(COPD)合并Ⅱ型呼吸衰竭患者的护理干预措施, 主要从无创正压通气护理、用药护理、肠内营养支持、管路护理、皮肤护理及心理护理等方面进行干预, 旨在改善患者呼吸衰竭状况和各项生命体征, 控制二氧化碳潴留病情, 减少并发症的发生。通过为患者提供恒定的、可调节的高速空氧混合气体, 冲刷患者呼气末残留在鼻腔、口腔及咽部的解剖无效腔的气体, 可明显减少患者下一次吸气时吸入的二氧化碳的含量。经鼻高流量氧疗序贯治疗的应用, 对低氧性呼吸衰竭患者具有积极的治疗效果。)